The Evil Seed - Harris, Joanne (London Black Swan, 2008)
It's never easy to face the fact that a man you once loved passionately has found the girl of his dreams, as Alice discovers when Joe introduces her to his new girlfriend. Then Alice finds an old diary and reads about two men and the mysterious woman who bewitched them both, buried in Grantchester churchyard half a century ago.
Include Note
Keywords: England--Cambridge